Pain without gain? A randomized crossover study on the impact of active and passive foam rolling on jump height and pain intensity - Heinke, Lars; Javanmardi, Sasha; Zemke, Janis Alexander; Rappelt, Ludwig; Freiwald, Jürgen; Baumgart, Christian; Niederer, Daniel (PeerJ, 2025)
Background Foam rolling has become increasingly popular for its proposed benefits on physical performance and recovery. This study investigated the effects of single bouts of active foam rolling and passive foam rolling on vertical jump height, perceived pain, and applied pressure during treatment. Methods Twenty physically active participants (10 males, 10 females) completed a randomized crossover design study, undergoing one active and one passive foam rolling session. Jumping performance was assessed via countermovement jump (CMJ) height at baseline, pre-treatment (PRE), and post-treatment (POST). Pain intensity was evaluated using a visual analog scale, while applied pressure was measured via force plates for active foam rolling and the weight applied to a custom device for passive foam rolling. Results The CMJ height post-treatment was reduced after both foam rolling treatments (p < 0.001, ωp2 = 0.29), with no significant interaction or condition effect observed. The applied pressure during active was significantly higher than during passive foam rolling for the thigh (p < 0.001, Hedges’ g = 1.14). In contrast, perceived pain was greater in passive than in active rolling (p = 0.002, Hedges’ g = 0.96). CMJ height improved following the initial warm-up (baseline to PRE, p = 0.014, 95%, Hedges’ g = −0.11). Conclusion This study highlights the biomechanical and psychological complexities of foam rolling, suggesting that both active and passive rolling may temporarily impair power performance. The observed jump height reduction could stem from decreased tissue stiffness, while the initial warm-up benefits reinforce the effectiveness of traditional warm-up protocols.
Keywords: Foam rolling; Myofascial release; Pain perception; Countermovement jump; Warm-up; Muscle